Measuring the impact of burn injury on the parent-reported health outcomes of children 1-to-5 years: Item pool development for the Preschool1–5 Life Impact Burn Recovery Evaluation (LIBRE) Profile. Issue 7 (November 2021) - Grant, Gabrielle G.; Brady, Keri J.S.; Stoddard, Frederick J.; Meyer, Walter J.; Romanowski, Kathleen S.; Chang, Philip H.; Painting, Lynda E.; Fowler, Laura A.; Nelson, Judith K.; Patel, Khushbu F.; Sheldrick, R. Christopher; Carter, Alice; et al.
Highlights: Pediatric burn recovery assessment metrics need to account for child growth. Computer adaptive tests (CAT) allow more efficient survey administration. Items were culled and developed to track burn recovery in children 1–5 years of age. Co-production was used to refine and optimize this large item pool. This item pool will serve as a foundation for a new preschool burn outcomes CAT. Abstract: Modern, reliable, and valid outcome measures are essential to understanding the health needs of young children with burn injuries. Burn-specific and age-appropriate legacy assessment tools exist for this population but are hindered by the limitations of existing paper-based instruments. The purpose of this study was to develop item pools comprised of questions appropriate for children aged 1–5 with burn injuries. Item development was based on a framework provided by previous work to develop the Preschool Life Impact Burn Recovery Evaluation (LIBRE) Conceptual Model. The Preschool LIBRE Conceptual Model work established four sub-domains of functioning for children with burns aged 1–5. Item development involved a systematic literature review, a qualitative item review process with clinical experts, and parent cognitive interviews. Four item pools were established: (1) communication and language development; (2) physical functioning; (3) psychological functioning and (4) social functioning for preschool-aged children with burn injuries. We selected and refined candidate items, recall periods, survey instructions, and response option choices through clinical and parental feedback during the qualitative review and cognitive interview processes. Item pools are currently being field-tested as part of the process to calibrate and validate the Preschool1–5 LIBRE Computer Adaptive Test (CAT) Profile.